Respuesta :
the answer is d) the mathematical work shown above is correctproof
a+b-2(ab-a) =Â a+b-2ab+2a =Â 3a+b-2ab
a+b-2(ab-a) =Â a+b-2ab+2a =Â 3a+b-2ab
Answer:
D- The mathematical work shown above is correct
Step-by-step explanation:
Given [tex]a+b-2(ab-a)[/tex],
Applying distributive property we get, [tex]a+b-2ab+2a[/tex]
Now collecting the like terms we get, [tex]3a+b-2ab[/tex] as [tex]a+2a=3a[/tex]
Now, we can see that the answer is correct and the student also did the right steps to get the answer. Â
[tex]a+b-2(ab-a)=a+b-2ab+2a[/tex] = [tex]3a+b-2ab[/tex]
Therefore, option D is correct. Â